2021
DOI: 10.1021/acsanm.1c03101
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Quantum Dot/MXene Nanoflake Hybrids for Ultraviolet Photodetectors

Abstract: Efficacious utility of fugacious photons within a limited dimension of photoactive semiconductor thin films provides a facile approach to break through the obstacle for the sensitivity improvement of photodetection. Herein, we demonstrate a facile way to fabricate ZnO quantum dot (QD)/MXene nanoflake photodetectors by uniformly blending various ratios of two-dimensional (2D) Ti 3 C 2 T x nanoflakes into ZnO QD thin films, which can establish a carrier transportation highway and light confinement centers within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…The photocurrent gradually increases with the UV-light density increasing. The relationship between the photocurrent and the light intensity can be fitted by a power law: , I = K P θ where K is the fitting constant, and θ represents the dependence of I on P . For photoconductive photodetectors, θ is typically between 0.5 and 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocurrent gradually increases with the UV-light density increasing. The relationship between the photocurrent and the light intensity can be fitted by a power law: , I = K P θ where K is the fitting constant, and θ represents the dependence of I on P . For photoconductive photodetectors, θ is typically between 0.5 and 1.…”
Section: Resultsmentioning
confidence: 99%
“…The photocurrent gradually increases with the UV-light density increasing. The relationship between the photocurrent and the light intensity can be fitted by a power law: 32,36…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Owing to the abundant terminations, MXene can be integrated with various active materials giving resultant composites that are promising materials for high-performance photodetectors. Combinations of MXenes with traditional photoresponsive materials, such as transition metal oxides, have been widely investigated and proved to further improve their performance [120,121,123,133]. For instance, Guo et al demonstrated that the deep ultraviolet (DUV) photovoltaic performance of the Zn 2 -GeO 4 crystal could be greatly enhanced by addition of 2D MXene flakes [120].…”
Section: Research: Reviewmentioning
confidence: 99%
“…The enhanced photoresponse performance are mainly due to the synergistic effect of Ti 3 C 2 and Zn 2 GeO 4 nanowires, where the conductive MXene promotes the carrier transport and the large contact interfaces accelerate the separation of electron-hole pairs. Li et al established an efficient carrier transportation channel by blending 0D ZnO QDs and 2D Ti 3 C 2 T x nanoflakes, which confines the light within the photoactive layers and enhances the sensitivity of photodetection [123]. Owing to the localized surface plasmon resonance effect of the MXene, the light absorption of ZnO/Ti 3 C 2 T x film is enhanced and an impressively improved EQE (150%) was achieved.…”
Section: Research: Reviewmentioning
confidence: 99%
“…Recently, ultraviolet photodetectors (UV PDs) has been widely used in the following fields, including ultraviolet guidance, fire detection, optical communications and medical applications [ 1 4 ]. Among the wide-bandgap semiconductors materials, ZnO is one of the best candidate materials for UV PDs due to its unique performance, such as wide direct bandgap (~ 3.3 eV) and high exciton binding energy (60 meV) [ 5 , 6 ], with excellent photoelectric conversion characteristics, thermal stability, nontoxic, easy preparation and inexpensive [ 1 , 7 , 8 ]. However, ZnO-based UV PDs still have the problems that weak light response [ 9 ] and response time longer [ 10 ], which limits its application in UV PDs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%